Metode Intervensi Dalam Terapi Bermain Origami Terhadap Perkembangan Kesehatan Mental, Emosi, Dan Perilaku Anak-Anak - Rahagia, Rasi; Suat, Hatty; Arda, Darmi; Haulussy, Rais Rahman; Kasmiati, Kasmiati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Playing origami is an activity of folding paper into a shape or picture by moving the hands while thinking. The purpose of this Community Service Activity is to provide a solution to the problems faced by school-age children through origami play therapy to improve children's fine motor skills. The method of this activity is an intervention in origami play therapy on the development of children's mental health, emotions, and behavior. The results of the implementation of Community Service activities, play therapy for children, went well and smoothly. The conclusion is that Community Service activities show that there is an increase in knowledge of new creations made by children and increase their insight into creativity in playing.